Lower‐Voltage Electroluminescence of Green Zinc Silicate on SiOx Interface in Metal–Oxide–Semiconductor Structure. Issue 21 (7th September 2021) - Kang, Taewook; Afandi, Mohammad M.; Kang, Hyeonwoo; Park, Jehong; Kim, Jongsu
Abstract : A Zn2 SiO4 :Mn 2+ ‐based metal–oxide–semiconductor electroluminescence (MOS EL) device on silicon wafer is demonstrated through a facile one‐step annealing process. The MOS EL device consists of two sublayers: 200 nm thick single‐phase crystalline Zn2 SiO4 :Mn 2+ for an emitting layer and 160 nm thick amorphous SiO x for interfacial layer as a carrier‐injecting–accelerating layer on a silicon wafer. It exhibits blueshift of the green EL peak with spectral broadening. According to applied polarities, it shows asymmetric electrical and optical properties. Eminently, it exhibits the best luminous efficiency of 1.2 lm W −1 at a comparatively lower threshold voltage (50 Vop corresponding to the electric field of 1.1 MV cm −1 ) and high reliability (>600 min at 70 Vop ). Abstract : A green Zn2 SiO4 :Mn 2+ ‐/SiOx ‐based metal–oxide–semiconductor electroluminescence device on a silicon wafer is demonstrated through a facile one‐step annealing process. According to alternating polarities, it shows asymmetric electrical and optical properties with a lower threshold voltage and higher reliability. This structure can be monolithically merged with light‐emitting silicon photonics.